Integrasi Moral Agama Dalam Pendidikan Budi Pekerti Melalui Pembelajaran Akidah Akhlak - Ahmad, Fikri; Ehwanudin, Ehwanudin; Anwar, Muhammad Saidun (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Education plays a crucial role in shaping the character of students so that they are not only intellectually intelligent but also have good morals. However, there are still many students who show behavior that does not reflect educational values, both in and outside of school. Lack of discipline, truancy, and disrespect towards teachers reflect that character education is still not optimal. Moral education in schools is an urgent need so that students have a better understanding of honesty, justice, and responsibility, which are fundamental values in religion and social life. Unfortunately, in practice, moral education is often only a transfer of knowledge without direct experience that can form a value system in students. Therefore, a more interactive and experience-based learning method is needed so that moral values can be more effectively embedded in students' lives. At MTs Tri Bhakti At-Taqwa Rama Puja, character education through learning of faith and morals has been implemented, but there are still obstacles in its implementation. Some students do not fully understand the importance of moral values, which can be seen from the lack of discipline and responsibility in carrying out learning activities. To overcome this, it is necessary to strengthen moral education through the integration of religious values with students' social lives. In addition, the role of family and society is also a determining factor in the success of moral education in schools. Effective moral education not only forms individuals who are faithful and pious, but also creates a young generation who have high moral awareness, behave ethically, and are able to contribute positively to society.